The role of interleukin 1 in the development of human diseases: focus on Anakinra (IL-1 receptor antagonist) - E. L. Nasonov; M. Yu. Samsonov (Научно-практическая ревматология)
According to modern concepts, human immune-mediated inflammatory diseases (IMIDs), depending on the prevailing mechanisms of immunopathogenesis, are divided into two main categories – autoimmune and autoinflammatory.At the same time, both autoimmune and autoinflammatory mechanisms are involved in the pathogenesis of most IMIDs, the complex interaction of which is reflected in the polymorphism of clinical manifestations, course variants, outcomes, and therapy efficacy. It is assumed that hyperproduction of cytokines of the interleukin (IL) 1 family, which is one of the key regulators of innate immunity, determines the “crossover” between the mechanisms of autoinflammation and autoimmunity in IMIDs. Anakinra is currently used in clinical practice to suppress the pathological effects of IL-1. An analysis of the results of the clinical use of Anakinra indicates that treatment with this drug should be considered as a promising direction in the pharmacotherapy of systemic autoinflammatory diseases (SAIDs) and critical conditions in children and adults associated with the development of hyperinflammation. The main directions of the Anakinra clinical research program are presented, including: determining the place of the drug in the implementation of the "Treat to Target" strategy and personalization of therapy, primarily in patients with “resistant” (difficult-to-treat) subtype of rheumatoid arthritis and comorbid pathology, as well as with severe forms of microcrystalline arthritis; the possibility of using Anakinra to improve the early diagnosis of SAIDs in children and adults; creation of the Russian register of patients with SAIDs, who are potentially indicated for treatment with Anakinra.